Identifying Pronunciation Errors of the Phoneme Qaf in Al-Qur’an Reading by Non-Native Speakers: A Spectrographic Analysis - Fadia, Falya; Al Farisi, Mohamad Zaka; Maulani, Hikmah (Faculty of Languages and Arts, Universitas Negeri Padang, 2024)
The accuracy of pronouncing Hijazi letters is crucial for reading the Qur'an effectively. Incorrect pronunciation not only disrupts the flow of reading but can also change the meaning of words and verses, thus deviating from the intended message. This study aims to identify and analyze the mispronunciation of the [q] phoneme by non-Arabic speakers using spectrography analysis. Spectrography analysis helps visualize the frequency, duration, and intensity of the sound produced when participants pronounce the [q] phoneme. The research utilized Praat Voice Analysis software version 6.3.17 to process voice recordings and identify differences in the pronunciation of the [q] phoneme. The research employed a comparative descriptive qualitative approach with a content analysis design. Data collection involved various techniques, including recording, listening, and transcription. Voice recordings of two 12-year-old participants and an Arabic native speaker were collected to compare the pronunciation of Surah Al-Falaq verses 1-3. The results indicated that common errors in this study included sound changes and the omission of the characteristic [q] phoneme. For instance, students often replaced the [q] phoneme with [k] due to the similarity in the articulation location of these two phonemes. Additionally, participants tended to read too quickly, not allowing sufficient time for accurate pronunciation. The study also revealed a significant difference in the articulation of Hijazi letters between male and female speaker. female speaker demonstrated more consistent pronunciation patterns, while male speaker may require further intervention to address articulation and phonological errors.